Genetic mutations in lymphocytic variant of hypereosinophilic syndrome: study of five siblings - Walkenhorst, Molly; Basu, Malay K.; Cui, Wei; Kumar, Manish; Vallurupalli, Anusha; Sitek, Andrea; Zhao, Xinyang; Zheng, X. Long; Zhang, Da (Frontiers in Medicine, 2025)
IntroductionLymphocytic variant hypereosinophilic syndrome (L-HES) is a rare subtype of hypereosinophilic syndrome driven by aberrant T-cell clones that promote eosinophilia through interleukin-5 (IL-5) overproduction. While clonal T-cell receptor (TCR) rearrangements are a hallmark, the underlying genetic landscape remains poorly defined.MethodsWe report a familial case series involving five siblings, three symptomatic and two asymptomatic, with comprehensive clinical, immunophenotypic, and genomic evaluations. Whole-exome sequencing (WES) was performed to identify rare germline variants contributing to disease susceptibility. The index patient (EOS1) presented with clonal CD3−CD4+ T cells, marked eosinophilia, and papillary thyroid carcinoma (PTC). Flow cytometry, TCR gene rearrangement studies, and a targeted 141-gene NGS panel were conducted, followed by whole-exome variant calling and annotation.ResultsEOS1 exhibited classic L-HES features and a positive TCR clonality test. Exome analysis revealed several nonsynonymous variants of uncertain significance in genes related to transcriptional regulation (ZNF257, MLLT1, BRD9), immune signaling (TESPA1, LRCH4, DHX58), and oncogenesis (CTAGE4, RGPD5). No STAT3 or recurrent mutations were identified. Several variants were shared among affected siblings but absent in unaffected controls, suggesting a possible hereditary predisposition.DiscussionThis study highlights novel germline variants potentially associated with L-HES pathogenesis and expands the genomic spectrum beyond previously implicated somatic mutations. Our findings support the role of immune dysregulation and genetic predisposition in L-HES and underscore the importance of broader genomic profiling in familial cases. Functional validation and long-term monitoring are essential for risk stratification and early detection of malignant transformation.